Impact of EdTech on Student Learning: Integration, Motivation, Literacy and Support - Thapa, Deepak; Thapa, Aashish (SAIM Journal of Social Science and Technology, 2025)
Purpose: This study examines the impact of educational technology on students’ learning outcomes, focusing on technology integration, student motivation and engagement, digital literacy, and institutional support and policies. Design/Methodology/Approach: Using a quantitative research design, data were collected from 317 students in Kathmandu Valley through purposive sampling. Regression analysis was conducted to evaluate the effects of these variables on learning outcomes. Findings: Results indicate that technology integration, student engagement and motivation, digital literacy, and institutional support and policies significantly and positively influence student learning outcomes. Implications: Insights from this study assist educational stakeholders in formulating effective strategies and policies to enhance technology use in learning environments, ultimately improving student experiences and outcomes. Originality: Grounded in engagement-driven technology integration and collaborative learning theories, this research offers novel empirical evidence on multiple factors affecting digital learning platforms and their role in student achievement, contributing to emerging literature in educational technology.